Kesediaan Siswa Sekolah sebagai Bystander Resusitasi Jantung Paru (RJP) di Kabupaten Jember - Wulansari, Yunita Wahyu; Wirasakti, Guruh (Jurnal Keperawatan Malang, 2023)
Background: Out-of-hospital cardiac arrest (OHCA) is a global health problem with a high incidence and mortality rate as well as survival rates. The willingness of the community as a bystander to perform CPR on victims of OHCA is an important factor in increasing the survival rate. Purpose: To identify the student’s willingness as bystanders Cardio Pulmonary Resuscitation (CPR) in Jember Regency. Methods: This research is a quantitative research with a cross-sectional approach in the form of analytical descriptive. The number of respondents was 245 students of class VIII SMP Negeri in Jember Regency using simple random sampling. Result: The results showed that the majority of school students were willing to do CPR as bystanders as much as 66.1%. The unavailability of school students as bystanders for Cardio Pulmonary Resuscitation (CPR) was influenced by experience and training, respectively, as much as 100% of the total 158 students who answered not willing. Conclusion: This study shows that the majority of students in SMP N Jember Regency are not willing to be CPR bystanders, so training or learning with appropriate methods is needed to increase the number of CPR bystanders who are willing to help victims of OHCA. Key words: bystander, CPR, students